Detoxification of hydroxylated polychlorobiphenyls by Sphingomonas sp. strain N-9 isolated from forest soil. (December 2016) - Mizukami-Murata, Satomi; Sakakibara, Futa; Fujita, Katsuhide; Fukuda, Makiko; Kuramata, Masato; Takagi, Kazuhiro
Abstract: To examine the biodegradation of hydroxylated polychlorobiphenyls (OH-PCBs), we isolated Sphingomonas sp. strain N-9 from forest soil using mineral salt medium containing 4-hydroxy-3-chlorobiphenyl (4OH-3CB) at the concentration of 10 mg/L. Following incubation with strain N-9, the concentration of 4OH-3CB decreased in inverse proportion to strain N-9 proliferation, and it was converted to 3-chloro-4-hydroxybenzoic acid (4OH-3CBA) after 1 day. We observed that strain N-9 efficiently degraded lowly chlorinated OH-PCBs (1–4 Cl), while highly chlorinated OH-PCBs (5–6 Cl) were less efficiently transformed. Additionally, strain N-9 degraded PCBs and OH-PCBs with similar efficiencies, and the efficiency of OH-PCB degradation was dependent upon the positional relationships between OH-PCB hydroxyl groups and chlorinated rings. OH-PCB biodegradation may result in highly toxic products, therefore, we evaluated the cytotoxicity of two OH-PCBs [4OH-3CB and 4-hydroxy-3, 5-dichlorobiphenyl (4OH-3, 5CB)] and their metabolites [4OH-3CBA and 3, 5-chloro-4-hydroxybenzoic acid (4OH-3, 5CBA)] using PC12 rat pheochromocytoma cells. Our results revealed that both OH-PCBs induced cell membrane damage and caused neuron-like elongations in a dose-dependent manner, while similar results were not observed for their metabolites. These results indicated that strain N-9 can convert OH-PCBs into chloro-hydroxybenzoic acids having lower toxicity. Graphical abstract: Highlights: Sphingomonas sp. strain N-9 utilizes chlorinated OH-PCBs and PCBs having 1–4 Cl. Strain N-9 degrades OH-PCBs and PCBs at imbalanced positions of chlorobiphenyl rings. Strain N-9 converts OH-PCBs into chloro-hydroxybenzoic acids having lower toxicity.